Emergencies in care for newborn in the first hour of life: A systematic literature review (Research, Society and Development, 2024)
Introduction: Emergency care for newborns in the first hour of life is provided to approximately 10% of live births in Brazil. The main occurrences are anoxia, meconium aspiration syndrome and respiratory distress syndrome. The conduct in these situations has been updated over the years and therefore a systematic review of such clinical practices is necessary. Objective: Analyze and correlate specific reference approaches, deepening the understanding of the complexities of emergencies in the first hours of life. Highlight root causes, early detection, treatments, and best practices for addressing critical situations. Methodology: This is a systematic literature review to list the main emergencies that occur during birth.  18 articles were analyzed from the following databases: Biblioteca Virtual em Saúde (BVS), Scielo, Lilacs and Latindex, referring to the years 2019 to 2023. Results: The evaluation of the studies revealed a diverse range of emergencies that can occur in the first hours of life, including thermoregulation, neonatal resuscitation procedures, respiratory complications, neonatal infections and congenital anomalies. Interconnections between studies are highlighted, emphasizing the importance of clinical knowledge and application of effective protocols to face neonatal emergencies. Conclusion: The research reiterates the urgency of early detection and adequate intervention in the face of neonatal emergencies in the first hours of life. Collaboration between medical disciplines and the application of evidence-based practices are vital to ensuring the survival and quality of life of newborns in the face of the critical challenges of this vital period.